2012
DOI: 10.1021/bi300918w
|View full text |Cite
|
Sign up to set email alerts
|

Seven Cysteine-Deficient Mutants Depict the Interplay between Thermal and Chemical Stabilities of Individual Cysteine Residues in Mitogen-Activated Protein Kinase c-Jun N-Terminal Kinase 1

Abstract: Intracellular proteins can have free cysteines that may contribute to their structure, function, and stability; however, free cysteines can lead to chemical instabilities in solution because of oxidation-driven aggregation. The MAP kinase, c-Jun N-terminal kinase 1 (JNK1), possesses seven free cysteines and is an important drug target for autoimmune diseases, cancers, and apoptosis-related diseases. To characterize the role of cysteine residues in the structure, function, and stability of JNK1, we prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Oxidized derivatives of free‐Cys residues, including formation of thiol adducts or cysteic acid, can effectively block refolding—resulting in an irreversible pathway that, by Le Chatelier's principle, will continuously drive protein unfolding. Consequently, buried free‐Cys residues can play a key role in regulating protein functional half‐life …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized derivatives of free‐Cys residues, including formation of thiol adducts or cysteic acid, can effectively block refolding—resulting in an irreversible pathway that, by Le Chatelier's principle, will continuously drive protein unfolding. Consequently, buried free‐Cys residues can play a key role in regulating protein functional half‐life …”
Section: Introductionmentioning
confidence: 99%
“…Conse-quently, buried free-Cys residues can play a key role in regulating protein functional half-life. [4][5][6][7][8] The presence of buried free-Cys residues in protein biopharmaceuticals, notably monoclonal antibodies, is problematic because they can effectively limit shelf-life as well as induce immunogenic aggregates. [9][10][11][12] A recent study of IgG1 and IgG2 antibodies showed that roughly one third of recombinant antibody molecules from a standardized industrial preparation contain a single open disulfide bond (that is, two free-Cys residues that should form a disulfide bond in the native state structure).…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine has unique chemical properties due to its side chain thiol group and can participate in a variety of functional roles such as disulfide bonding, hydrogen bonding and redox regulation . While disulfide bonds play important roles for protein structure and stability, functional roles of free cysteines often depend on their positions and local environment in the protein, and whether it is interior or solvent exposed . We performed a systematic study in this work by replacing each Cys in the rhαGal protein, including the two free Cys, to examine their impact on protein expression, structure, activity and stability.…”
Section: Discussionmentioning
confidence: 99%
“…In general, free cysteines have been found to play a variety of roles in protein structure and function, including dimerization, metal coordination, enzyme catalysis, redox regulation and thermal stability . The function of the cysteine residue appears to largely depend on its chemical environment within the folded protein structure and has been studied particularly for enzymes involved in lysosomal storage diseases . In rhαGal, the two free cysteines occupy different structural environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation